Babesia parasitemia rebound after red blood cell exchange. Issue 4 (1st September 2016) - Alquist, Caroline R.; Szczepiorkowski, Zbigniew M.; Dunbar, Nancy
Abstract: Babesiosis is an increasingly recognized disease which may benefit from therapeutic apheresis (Category II/Grade 2C). Vulnerable populations include the splenectomized, those aged >50, those with malignancies, and the immunocompromised. In the setting of parasite levels > 10%, significant anemia, renal impairment, pulmonary compromise, or hepatic dysfunction, RBC exchange can rapidly reduce parasite burdens and decrease the bioavailability of proinflammatory cytokines. No previous report has shown such a rapid rebound in parasitemia despite adequate organism removal. Herein, we report a case of severe babesiosis in a splenectomized 56 year old male with a past medical history significant for benign multiple sclerosis. Following a week of flu‐like symptoms, the patient presented to an outside hospital with anemia, elevated bilirubin, thrombocytopenia, and 15% of his RBCs containing Babesia forms on a peripheral smear. Despite initiation of appropriate antimicrobials, subsequent transfer to our facility revealed worsening parasitemia (25%), tachypnea, and hypoxia. An emergent two volume RBC exchange was performed, resulting in 15% post‐exchange parasitemia. Twelve hours later, the parasitic burden had climbed to 30%. A second RBC exchange reduced the parasite burden to 1.5%. His post‐procedural course was significant for diminishing periodic increases in parasitemia despite continued antimicrobial therapy. Rapid increases in parasitic burden following RBC exchanges can occur and post‐procedural surveillance of parasitemia should be closely monitored to expedite additional exchanges.